2019
DOI: 10.1111/jace.16385
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic dielectric properties of columbite ZnNb2O6 ceramics studied by P–V–L bond theory and Infrared spectroscopy

Abstract: In this study, intrinsic dielectric properties of ZnNb2O6 ceramics were investigated using P–V–L chemical bond theory and far‐infrared reflectivity spectra. The largest bond ionicity and bond susceptibility of Nb–O bonds suggest that the dielectric polarizability is mainly determined by Nb–O bonds. Relative permittivity, calculated via P–V–L bond theory, is close to experimental value determined using TE011 mode. The Nb–O bonds are also crucial for the structural stability. According to far‐infrared reflectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…From the point of view of crystal structure and P-V-L bond theory, an attractive feature of this system is that three distinc- It is necessary to investigate the structural impacts via P-V-L bond theory due to the three types of crystal structures showing large diversities in microwave dielectric properties. Based on a consideration of bonding environments and charge distributions, the binary bonding formulas for the three structures can be summarized as: 224,225 Detailed comparisons between bond ionicity and lattice energy can be found in Table 8S in ESI. † Here we summarize the average bond ionicity, total lattice energy and microwave dielectric properties of (Zn 1/3 Nb 2/3 ) x Ti 1−x O 2 (x = 0.45, 0.75, 1) systems in Table 18.…”
Section: Zno-tio 2 -Nb 2 O 5 Ternary Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of crystal structure and P-V-L bond theory, an attractive feature of this system is that three distinc- It is necessary to investigate the structural impacts via P-V-L bond theory due to the three types of crystal structures showing large diversities in microwave dielectric properties. Based on a consideration of bonding environments and charge distributions, the binary bonding formulas for the three structures can be summarized as: 224,225 Detailed comparisons between bond ionicity and lattice energy can be found in Table 8S in ESI. † Here we summarize the average bond ionicity, total lattice energy and microwave dielectric properties of (Zn 1/3 Nb 2/3 ) x Ti 1−x O 2 (x = 0.45, 0.75, 1) systems in Table 18.…”
Section: Zno-tio 2 -Nb 2 O 5 Ternary Systemsmentioning
confidence: 99%
“…42. 225 The real part and imaginary part of the complex dielectric constant fitted using a classical three-parameter model (LTPC) and a four-parameter semiquantum model (FPSQ) are shown in Fig. 43.…”
Section: Zno-tio 2 -Nb 2 O 5 Ternary Systemsmentioning
confidence: 99%
“…The relative density, relative permittivity, and quality factor all reach to maximum value when sintered at 725°C. As known, [26][27][28] extrinsic factors including pores, secondary phase, defects, and intrinsic factors originated from dielectric polarization and lattice vibration mutually dominate the variation of ε r and Q × f value. Extrinsically, the variations of relative permittivity and Q × f value are consistent with the shift of densification.…”
Section: Correlation Between Chemical Bond Characteristic and Micromentioning
confidence: 98%
“…ZnNb 2 O 6 ceramics prepared by microwave sintering exhibited relative density of 94.3%, and the quality factor was dominated by the distribution of grain size [155]. Recently, the intrinsic dielectric properties were investigated using chemical bond theory and lattice vibrational spectra, which indicated that B 1u mode at 168.87 cm -1 was highly related to the dielectric properties [156], and the fitted results of infrared-related spectrum are presented in Fig. 7.…”
Section: Rutile-trirutile/ixiolite/wolframite-columbite Type Ceramicsmentioning
confidence: 99%